Paul's eschatological anthropology : the dynamics of human transformation - Harding, Sarah (Emerging scholars., 2015)
Sarah Harding examines Paul's anthropology from the perspective of eschatology, concluding that his view of humans depends on his belief that the cosmos evolves through distinct aeons in progress towards its telos. Harding describes a temporal distinction of the old aeon, the new aeon, and the significant overlap of aeons in which those "in Christ" dwell, eschatological dimensions that determine the value Paul attaches to any particular anthropological "aspect," then examines the cosmological power dominant in each aeon and the structures through which, in Paul's view, these influence human be.